Analisis Kehilangan Energi (Head Loss) Pada Saluran Drainase U-Ditch Ukuran 40x60 Di Jalan Cemara XII, Kota Kediri - Moh. Ali Maftuh; Sony Susanto (Jurnal Konstruksi, 2025)
This study analyzes energy loss (head loss) in a 40×60 cm U-Ditch drainage channel on Jalan Cemara XII, Kediri City. The methods used are quantitative approaches with hydrological (Mononobe, Rational) and hydraulic (Manning, Darcy–Weisbach) calculations. The results show a planned discharge of 0.07985 m³/s, a flow velocity of 1.3369 m/s, and a total energy loss of 2.20 m. Comparison with field data shows a difference of 3.77%, which means that this analysis model is valid. The channel capacity safety factor reaches 4.0 and the flow is subcritical (Fr = 0.96). This study provides a scientific basis for evaluating the hydraulic efficiency of precast channels and can be developed into a real-time monitoring-based Smart Drainage system.